Decompositions of Quaternions and Their Matrix Equivalents - Janovská, Drahoslava; Opfer, Gerhard (Matrix Methods: Theory, Algorithms And Applications, 2010)
Since quaternions have isomorphic representations in matrix form we investigate various well known matrix decompositions for quaternions.